Beyond the Bauhaus : Cultural Modernity in Breslau, 1918-33 - Barnstone, Deborah Ascher (Book collections on Project MUSE., 2016)
"The Breslau arts scene during the Weimar period was one of the most vibrant in all of Germany, yet it has disappeared from memory and historiography. Breslau was a key center for innovative artistic production during the Weimar Republic; recovery of its history will shed new light on German cultural dynamics in the 1920s. Such a study has art historical significance because of the incredible extent of innovation that occurred in almost every intellectual field, advances that formed the basis for aesthetic modernism internationally and continue to affect the course of visual art and architecture today. Architecture education, just one example in many, is still largely based on a combination of the Bauhaus model from the 1920s and the model developed at the Breslau Academy of Fine and Applied Art. The exploratory attitude encouraged in Weimar era arts endeavors, as opposed to the conformism of academic art, is still a core value promoted in contemporary art and architecture circles. Given the long-lasting influence of Weimar culture on modernism one would expect to find a spate of studies examining every aspect of its cultural production, but this is not the case. Recent scholarship is almost exclusively focused on Berlin and the Dessau Bauhaus. Although both interests are understandable, the creative explosion was not confined to these cities but was part of a larger cultural ethos that extended into many of the smaller regional centers. The Expressionist associations the Blaue Reiter in Munich and Brücke in Dresden are two well-known examples. Equally, innovation was not confined to a few monumental projects like the Stuttgart Weissenhofsiedlung but part of a broader national cultural ethos. The dispersion of modernism occurred partly because of the political history of Germany as a loosely joined confederation of small city states and principalities that had strong individual cultural identities before unification in 1871 but also because of the German propensity to value and take intense pride in the Heimat, understood both as the hometown and the region. Heimatliebe translated into generous support for cultural institutions in outlying cities. Host to a roster of internationally acclaimed artists and architects, major collectors, arts organizations, museums, presses, galleries, and one of the premier German arts academies of the day, Breslau boasted a thriving modern arts scene until 1933 when the Nazis began their assault on so-called 'degenerate' art. This book charts the cultural production of Breslau-based artists, architects, art collectors, urban designers, and arts educators, who were especially interesting because they operated in the space between the margins of Weimar-era cultural debates. Rather than accepting the radical position of the German avant-garde or the reactionary position of German conservatives, many Breslauers sought a middle ground. It is the first book in English to address this history and presents the history in a manner unique to any studies currently on the market. Beyond the Bauhaus explores the polyvalent and contradictory nature of cultural production in Breslau in order to expand the cultural and geographic scope of Weimar history; the book asserts a reciprocal dimension to the relationship between regional culture and national culture, between centers like Breslau and the capital Berlin. With major international figures like the painters Otto Mueller and Oskar Moll, architects Hans Scharoun and Adolf Rading, urban planners Max Berg and Ernst May, collectors Ismar Littmann and Max Silberberg, and an art academy that by 1929 was considered the best in Germany, Breslau clearly had significance to narratives of Weimar cultural production. Beyond the Bauhaus contributes the history of German culture during the Weimar Republic. It belongs alongside histories of art, architecture, urban design, exhibition, collecting, and culture; histories of the Bauhaus; histories of arts education more broadly; and German history. The readership would include those interested in German history; German art, architecture, urban design, planning, collecting, and exhibition history; in the avant-garde; the development of arts academies and arts pedagogy; and the history of Breslau and Silesia"--Google Books